A bifunctional sensor based on diarylethene for the colorimetric recognition of Cu2+ and fluorescence detection of Cd2+. Issue 50 (17th September 2019) - Qiu, Shouyu; Lu, Mengmeng; Cui, Shiqiang; Wang, Zhen; Pu, Shouzhi
Abstract : A bifunctional sensor for colorimetric recognition of Cu 2+ and fluorescent detection of Cd 2+ was synthesized. It not only showed high selectivity and sensitivity to Cu 2+ and Cd 2+, but also could be used in practical water samples with high accuracy. Abstract : A novel bifunctional sensor based on diarylethene with a benzyl carbazate unit was synthesized successfully. It not only served as a colorimetric sensor for the recognition of Cu 2+ by showing changes in absorption spectra and solution color, but also acted as a fluorescent sensor for the detection of Cd 2+ through obvious emission intensity enhancement and fluorescence color change. The sensor exhibited excellent selectivity and sensitivity towards Cu 2+ and Cd 2+, and the limits of detection for Cu 2+ and Cd 2+ were 8.36 × 10 −8 mol L −1 and 1.71 × 10 −7 mol L −1, respectively, which were much lower than those reported by the WHO and EPA in drinking water. Furthermore, its application in practical samples demonstrated that the sensor can be effectively applied for the detection of Cu 2+ and Cd 2+ in practical water samples.